Insights into N-doping in single-walled carbon nanotubes for enhanced activation of superoxides: A mechanistic study - Duan, X.; Ao, Z.; Sun, Hongqi; Zhou, L.; Wang, G.; Wang, S. (2015)
Emerging characteristics upon nitrogen-doping were differentiated in the activation of superoxides over single-walled carbon nanotubes. Both experimental and theoretical studies revealed that enhanced peroxymonosulfate (PMS) activation is ascribed to a nonradical process while persulfate (PS) activation is accelerated via directly oxidizing water, yet hydrogen peroxide (H2O2) activation is inert to N-doping. This study details the first insights into versatile N-doping in carbocatalysis for organic oxidation in sustainable remediation.